Sistem Kontrol Dan Monitoring Suhu Dan Kelembaban Udara Pada Fermentasi Tempe Menggunakan Modul ESP8266 Dengan Platform Iot - Fitri Wulandari; Ery Safrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
One of traditional foods of Indonesian people is tempe. Tempe is made from fermented soybeans with Rhizopus Oligosporus mold. In its production, producers’ tempe often fail. One of them is Harber Tempe Factory, located in Pelita Street, Pekanbaru City. Beside weather factors, there are no supporting tools for temperature and humidity detection at the factory, also become obstacles in fermentation process of tempe. Producers’ tempe do not know exactly how much temperature and humidity must be maintained for fermentation process. Manufacturers only can estimate temperature and humidity in fermentation room. If temperature is considered too hot, producers’ tempe will come to factory and open air pentilation. So, the room temperature is back to normal because house of producer’s tempe and tempe factory are separate.Tools used in this study are ESP8266 Module, DHT22, Relay, Power Bank as power, fan and battery. Internet of Things (IoT) is a concept where objects in physical form can be connected and can transfer data through internet network by sensors. The concept of IoT describes every object that can be connected to internet and can be controlled remotely without having to be in that place. With IoT, job will be made faster and easier. The results obtained from the test are if temperature and humidity are above or below of normal temperature (250C-320C), a notification will appear on user's smartphone via Blynk application. If temperature is too hot, fan will turn on automatically. If temperature is too cold, light will turn on. Monitoring data can be viewed on thingspeak in graphical form. Keywords: Monitoring, Blynk, Thingspeak, ESP8266,Internet of Things